PENGEMBANGAN EKOKRITIK SASTRA DALAM PEMBELAJARAN PUISI HIJAU (KAJIAN TEORETIS) - Rokhmah, Akhirul Insan Nur (Universitas Negeri Surabaya, 2022)
Many of the environmentalists who advise the industrial community to continue to make sustainable development that pay attention to environmental conditions. However the economic and social interests of the community make environmental problems worse. Literature can play a role in saving the environment. Ecocritical development through green poetry in junior and senior high school students is needed so that the younger generation understands green literature. The originality of the natural environment will be maintained because it increases awareness of nature even though it is teetering due to various interests of the political elite. The purpose of this study is to explain the concept of the development of literary ecocritics in learning green poetry. The method used in this research is grounded theory and descriptive qualitative with data collection in the form of literature study. The data comes from several condition, literary and environmental theories that are collected and accumulated with basic literary competencies then adjusted to literary ecocritical learning to produce the syntax of learning green poetry. The results of the research in the form of the syntax of learning green poetry in broad outline are to foster student interest, read per sentence, write poetry, and demonstrate poetry.